Prescription patterns of supportive care medications among children receiving chemotherapy treatments at a major referral hospital in Tanzania: where are we in managing chemotherapy-induced toxicities? - Katabalo, Deogratias M.; Abraham, Melina; Kidenya, Benson R.; Liwa, Antony; Schroeder, Kristin (Frontiers in Oncology, 2025)
BackgroundCancer chemotherapy is a treatment that systematically kills cancer cells but causes expected side effects, known as chemotherapy-induced toxicities. These toxicities are managed with supportive care medications. This study aimed to determine the prescription patterns of supportive care medications in children receiving chemotherapy at a major referral hospital in Tanzania.MethodologyA hospital-based descriptive cross-sectional study was conducted at Bugando Medical Centre (BMC). The study analyzed 104 prescription slips of pediatric cancer patients receiving chemotherapy and qualitatively assessed national guidelines and disease-specific protocols used in guiding treatment. Data were cleaned in Microsoft Excel, analyzed using STATA version 15, and presented as frequencies, percentages, and narrative summaries.ResultsOndansetron (84.6%) and pre-hydration normal saline (20.2%) were the most prescribed pre-chemotherapy supportive care medications. Similarly, oral ondansetron (80.8%) and post-hydration normal saline (22.1%) were the most prescribed post-chemotherapy medications. Few prescriptions included a combination of antiemetics, fluids, and proton pump inhibitors for regimens with multiple chemotherapeutic agents. National cancer treatment guidelines lacked detailed sections on supportive care medications, leaving prescribing decisions to clinicians, while Burkitt’s lymphoma and nephroblastoma protocols offered more detailed guidance.ConclusionAntiemetics and hydration fluids dominated supportive care prescriptions. Significant gaps were identified in the inclusion of supportive care in national guidelines, with reliance on disease-specific protocols. These findings highlight the need for standardized, evidence-based supportive care guidelines tailored to resource-limited settings.